Strategies for addressing the university library users’ changing needs and practices in Sub-Saharan Africa - Musoke, Maria G.N. (The Journal of Academic Librarianship, 2008)
The paper presents a Sub-Saharan African academic Librarian’s experience in trying to address the changing needs and practices of university library users. Special reference is made to Makerere University Library. Most of the changes have been brought about by the various paradigm shifts in teaching, learning and research, as well as advances in information systems and services resulting from developments in Information and Communication Technologies (ICTs). Achievements and challenges are highlighted
Keywords: university library; users; Sub-Saharan Africa